Making Unhealthy Places : the Built Environment and Non-Communicable Diseases in Khayelitsha, Cape Town (2016)
ABSTRACT: In this paper, we examine how economic, social and political forces impact on NCDs in Khayelitsha (a predominantly low income area in Cape Town, South Africa) through their shaping of the built environment. The paper draws on literature reviews and ethnographic fieldwork undertaken in Khayelitsha. The three main pathways through which the built environment of the area impacts on NCDs are through a complex food environment in which it is difficult to achieve food security, an environment that is not conducive to safe physical activity, and high levels of depression and stress (linked to, amongst other factors, poverty, crime and fear of crime). All of these factors are at least partially linked to the isolated, segregated and monofunctional nature of Khayelitsha. The paper highlights that in order to effectively address urban health challenges, we need to understand how economic, social and political forces impact on NCDs through the way they shape built environments.